Partnered sexual activity moderates menstrual cycle-related changes in inflammation markers in healthy women: An exploratory observational study - Lorenz, Tierney K. (Fertil Steril, 2016)
OBJECTIVE: To examine differences in inflammation markers in sexually active vs. abstinent women, and observe changes in inflammation markers across the menstrual cycle. Cycle-related immune fluctuations may have evolved to reduce interference with conception. If so, reproductively active (i.e., sexually active) women should show the most variability in cytokine expression. DESIGN: Participants provided serum samples at menses and ovulation (from which cytokines were assayed) and saliva samples at menses, follicular, ovulation, and luteal phases (from which C-reactive protein was assayed). Participants self-reported intercourse frequency during the study. SETTING: Academic research laboratory. PARTICIPANTS: 32 healthy, naturally cycling premenopausal women (sexually active, N = 15, abstinent, N = 17). INTERVENTIONS: Observational study. MAIN OUTCOME MEASURES: Pro-inflammatory cytokines (Interleukin-6, IL-6; Interferon γ, IFN-γ; Tumor Necrosis Factor α, TNF-α), an anti-inflammatory cytokine (Interleukin-4, IL-4), and a marker of total inflammation (C-reactive protein, CRP). RESULTS: Sexually active women had higher levels of all of the immune markers measured, including both pro- and anti-inflammatory cytokines, than abstinent women. Relative to sexually active women, abstinent women had less change across the menstrual cycle in levels of CRP. Among sexually active women, higher intercourse frequency predicted greater mid-cycle decreases in CRP, IL-6, and IFN-γ and mid-cycle increases in IL-4. CONCLUSIONS: Sexual activity may stimulate a complex interaction between pro- and anti-inflammatory cytokines that subsequently drive mid-cycle declines in inflammation.